Formaldehyde impairs transepithelial sodium transport - Cui, Yong (Sci Rep, 2016)
Unsaturated oxidative formaldehyde is a noxious aldehyde in cigarette smoke that causes edematous acute lung injury. However, the mechanistic effects of formaldehyde on lung fluid transport are still poorly understood. We examined how formaldehyde regulates human epithelial sodium channels (ENaC) in H441 and expressed in Xenopus oocytes and exposed mice in vivo. Our results showed that formaldehyde reduced mouse transalveolar fluid clearance in vivo. Formaldehyde caused a dose-dependent inhibition of amiloride-sensitive short-circuit Na(+) currents in H441 monolayers and of αβγ-ENaC channel activity in oocytes. α-ENaC protein was reduced, whereas phosphorylation of the extracellular regulated protein kinases 1 and 2 (ERK1/2) increased significantly post exposure. Moreover, both α- and γ-ENaC transcripts were down-regulated. Reactive oxygen species (ROS) was elevated significantly by formaldehyde in addition to markedly augmented membrane permeability of oocytes. These data suggest that formaldehyde contributes to edematous acute lung injury by reducing transalveolar Na(+) transport, through decreased ENaC activity and enhanced membrane depolarization, and by elevating ROS production over long-term exposure.